2020
DOI: 10.1002/anie.202002208
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)‐Catalyzed Atroposelective Synthesis of Biaryls by C−H Activation and Intermolecular Coupling with Sterically Hindered Alkynes

Abstract: Reported herein is the atroposelective synthesis of biaryl NH isoquinolones by RhIII‐catalyzed C−H activation of benzamides and intermolecular [4+2] annulation for a broad scope of 2‐substituted 1‐alkynylnaphthalenes, as well as sterically hindered, symmetric diarylacetylenes. The axial chirality is constructed based on dynamic kinetic transformation of the alkyne in redox‐neutral annulation with benzamides, with alkyne insertion being stereodetermining. The reaction accommodates both benzamides and heteroaryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 141 publications
0
53
1
Order By: Relevance
“…Additionally, scale-up synthesis of 3 (1 mmol) was successful, with essentially no deterioration of enantioselectivity. Comparable efficiency and enantioselectivity (84-93 % ee) were also realized for a series of meta-substituted alkynes (11)(12)(13)(14). While ortho-substituted alkynes generally exhibited poor efficiency due to steric effect, presence of ortho F groups in the alkyne was tolerated (15).…”
Section: Indolesarewell-knownstructuralmotifsinalargenumberofmentioning
confidence: 89%
See 2 more Smart Citations
“…Additionally, scale-up synthesis of 3 (1 mmol) was successful, with essentially no deterioration of enantioselectivity. Comparable efficiency and enantioselectivity (84-93 % ee) were also realized for a series of meta-substituted alkynes (11)(12)(13)(14). While ortho-substituted alkynes generally exhibited poor efficiency due to steric effect, presence of ortho F groups in the alkyne was tolerated (15).…”
Section: Indolesarewell-knownstructuralmotifsinalargenumberofmentioning
confidence: 89%
“…Waldmann reported intramolecular redox-neutral [4+2] annulation of benzamides bearing a pendant alkyne using a chiral JasCpRh III catalyst, [12] and our group recently developed an intermolecular version. [13] Meanwhile, Wang disclosed Rh III -catalyzed [2+2+2] carboannulation between N-arylindolinones and alkyne. [14] Nevertheless, these very few reports [12][13][14] are limited to 6,6-biaryl synthesis due to reactivity challenge posed by employment of bulky directing group and/or coupling reagent.…”
Section: Indolesarewell-knownstructuralmotifsinalargenumberofmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49 ] Recently, the same group used 1‐alkynyl‐2‐naphthyl ethers 70 as coupling partners with N‐OPiv ‐hydroxamate 13 . [ 50 ] The reactions were performed with chiral RhCp x complex 71 and afforded the biaryl derivatives 72 . Once again with a broad scope of substrates and a variety of functional groups (Scheme 16c).…”
Section: Transition‐metal Chiral Cpx Complexesmentioning
confidence: 99%
“… 11 We have described an intramolecular C–H functionalization of aromatic compounds with alkynes forming axially chiral 4-arylisoquinolones catalyzed by chiral Rh Jas Cp complexes, 12 and Li et al recently reported the use of chiral RhCp x complexes in the synthesis of axially chiral biindolyls. 13 To the best of our knowledge, there is no general enantioselective method that enables the construction of atropisomers containing a five-membered aromatic ring (furans, thiophenes, and pyrroles). Herein, we report the Rh Jas Cp-catalyzed enantioselective synthesis of these five-membered-ring atropisomers via direct C–H functionalization with 1-diazonaphthoquinones ( Scheme 1 c, bottom).…”
mentioning
confidence: 99%